(untitled) (Global Journals of Research in Engineering, 2011)
Nowadays in order to achieve environmental goals renewable energy sources especially wind has been seemed useful while wind generation does not directly produce air pollutants emission So it seems necessary to consider air pollutants emission level in windthermal scheduling problems This paper proposes two methodologies for wind thermal scheduling in a power system with high penetration of wind power subject to consider air pollutants emission reduction Also a stochastic programming market-clearing model has been applied for solving unit commitment problem to overcome stochastic nature of power In this stochastic security model wind generation uncertainty is modeled by scenario tree in scheduling time horizon The usefulness of the proposed approach was demonstrated through an IEEE 30- bus test system over 6 hours